Absence of the Fragile X Mental Retardation Protein results in defects of RNA editing of neuronal mRNAs in mouse. Issue 11 (2nd November 2017) - Filippini, Alice; Bonini, Daniela; Lacoux, Caroline; Pacini, Laura; Zingariello, Maria; Sancillo, Laura; Bosisio, Daniela; Salvi, Valentina; Mingardi, Jessica; La Via, Luca; Zalfa, Francesca; Bagni, Claudia; et al.
ABSTRACT: The fragile X syndrome (FXS), the most common form of inherited intellectual disability, is due to the absence of FMRP, a protein regulating RNA metabolism. Recently, an unexpected function of FMRP in modulating the activity of Adenosine Deaminase Acting on RNA (ADAR) enzymes has been reported both in Drosophila and Zebrafish. ADARs are RNA-binding proteins that increase transcriptional complexity through a post-transcriptional mechanism called RNA editing. To evaluate the ADAR2-FMRP interaction in mammals we analyzed several RNA editing re-coding sites in the fmr1 knockout (KO) mice. Ex vivo and in vitro analysis revealed that absence of FMRP leads to an increase in the editing levels of brain specific mRNAs, indicating that FMRP might act as an inhibitor of editing activity. Proximity Ligation Assay (PLA) in mouse primary cortical neurons and in non-neuronal cells revealed that ADAR2 and FMRP co-localize in the nucleus. The ADAR2-FMRP co-localization was further observed by double-immunogold Electron Microscopy (EM) in the hippocampus. Moreover, ADAR2-FMRP interaction appeared to be RNA independent. Because changes in the editing pattern are associated with neuropsychiatric and neurodevelopmental disorders, we propose that the increased editing observed in the fmr1- KO mice might contribute to the FXS molecular phenotypes.